PENERAPAN MEDIA FILM “NUSSA DAN RARA” PADA MATA PELAJARAN PENDIDIKAN PANCASILA FASE A DI SDN SUMUR WELUT III/440 SURABAYA - Shinta Ika Wati; Rarasaning satianingsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The animated film Nussa and Rara is a communication medium in the form of cartoon-style images or more precisely depicted cartoon characters which are very effective in conveying ideas in a unique way to provide inspiration, and also contains Pancasila education material, especially for elementary school students. This research aims to describe the extent to which Phase A teachers and students at SDN Sumur Welut III/440 Surabaya are able to apply the film media